2016
DOI: 10.1248/cpb.c15-00795
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and SAR Studies of Neuritogenic Gentiside Derivatives

Abstract: Tetradecyl 2,3-dihydroxybenzoate (ABG-001) has been designed and synthesised as a lead compound to treat Alzheimer's disease, based on structure-activity relationships of gentisides. In this paper, the alkyl chain and ester linkage group of ABG-001 were modified. Consequently, several series of novel gentiside derivatives were designed and synthesised, and their neuritogenic activity was evaluated in PC12 cells. Among all the tested compounds, S-dodecyl 2,3-dihydroxybenzothioate (15d, named as ABG-199) was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…On the contrary, the chain length is important for activity. In the benzoate series, higher activity was found for derivatives with alkyl chains containing 8–16 carbon atoms (i.e., 13–21 bonds between the two catechol rings) , . So, in order to get ligands able (i) to chelate with high affinity the biologically relevant redox metal ions Cu 2+ and Fe 3+ , and (ii) to promote NGF‐like activity, we designed and synthesized a series of tetradentate bis(2,3‐dihydroxyalkylbenzamide) derivatives having 10–13 bonds between the two catechol rings (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the chain length is important for activity. In the benzoate series, higher activity was found for derivatives with alkyl chains containing 8–16 carbon atoms (i.e., 13–21 bonds between the two catechol rings) , . So, in order to get ligands able (i) to chelate with high affinity the biologically relevant redox metal ions Cu 2+ and Fe 3+ , and (ii) to promote NGF‐like activity, we designed and synthesized a series of tetradentate bis(2,3‐dihydroxyalkylbenzamide) derivatives having 10–13 bonds between the two catechol rings (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, this motif is of potential interest for the therapy of neurodegenerative diseases, and series of synthetic 2,3‐dihydroxybenzoates and 2,3‐dihydroxythiobenzoates were synthesized. Their activity as neurite outgrowth inducers, compared to that of NGF, was found to be promising in vitro , …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the mechanism of the action of AMA for its NGF-mimicking effect was different from that of previously reported compounds (such as ABG-001, lindersin B, 3beta,23,28-trihydroxy-12-oleanene 3beta-caffeate and CuB). Tetradecyl 2,3-dihydroxybenzoate (ABG-001) was designed and synthesized as a lead compound in accordance with the gentiside series to induce neurogenesis in PC12 cells by the IGF-1R/PI3K/MAPK signaling pathway [9,10]. Lindersin B from L. crustacea induced neuritogenic activity through the activation of the TrkA/PI3K/ERK signaling pathway [11].…”
Section: Discussionmentioning
confidence: 99%
“…Given the characteristic of exhibiting sympathetic neuron-like phenotypes under the stimulation of the NGF, the PC12 cell line, which is derived from rat pheochromocytoma cells, is widely used as a model to screen small molecules with NGF-mimicking activities [6]. In previous studies, under the guidance of a PC12 cell bioassay system, several small molecules with NGF-mimicking activities were isolated from traditional Chinese medicines (TCMs) such as Gentiana rigescens Franch, Lindernia crustacean and Desmodium sambuense and the mechanism of the action studies was also identified [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] To date, we have isolatedo rsynthesized dozenso fn euritogenic substances. [12][13][14][15][16] To identify new highly effective substances that exhibit low toxicitya nd novel mechanisms,w eh ave steadily pursued the extractiona nd separation of traditional Chinese medicines (TCMs) and synthesized derivatives for structure-activity relationship (SAR) studies. Desmodium sambuense,w hich belongs to the Leguminosae family, is an important TCM.…”
Section: Introductionmentioning
confidence: 99%